2021
DOI: 10.3389/fvets.2021.794024
|View full text |Cite
|
Sign up to set email alerts
|

Liver- and Spleen-Specific Immune Responses in Experimental Leishmania martiniquensis Infection in BALB/c Mice

Abstract: Leishmania martiniquensis is a neglected cause of an emerging leishmaniasis in many countries, including France, Germany, Switzerland, the United States of America, Myanmar, and Thailand, with different clinical manifestations ranging from asymptomatic, cutaneous (CL), visceral (VL), and atypically disseminated CL and VL. The persistence of parasites and the recurrence of the disease after treatment are challenges in controlling the disease. To explore efficient prophylaxis and therapy, this study aimed to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…[12][13][14] Moreover, a spleen-liver axis has been defined to describe the crosstalk between the spleen and liver. [15][16][17] Spleen-derived cytokines including transforming growth factor-β1 (TGF-β1), IL-10, and TNF, [18][19][20] chemokine like CCL2, [21] and factors involved in metabolic activities [16,22] have been shown to play essential roles in linking the spleen and liver. [23] Yet, little evidence is provided for splenocytes acting as mediators of the spleen-liver axis, although a few studies in liver diseases have demonstrated altered composition of hepatic immune cells upon splenectomy.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Moreover, a spleen-liver axis has been defined to describe the crosstalk between the spleen and liver. [15][16][17] Spleen-derived cytokines including transforming growth factor-β1 (TGF-β1), IL-10, and TNF, [18][19][20] chemokine like CCL2, [21] and factors involved in metabolic activities [16,22] have been shown to play essential roles in linking the spleen and liver. [23] Yet, little evidence is provided for splenocytes acting as mediators of the spleen-liver axis, although a few studies in liver diseases have demonstrated altered composition of hepatic immune cells upon splenectomy.…”
Section: Introductionmentioning
confidence: 99%